EVALUASI PROGRAM KAMPUNG TEMATIK DALAM MENDORONG PENINGKATAN PEREKONOMIAN MASYARAKAT STUDI DI KAMPUNG TEMATIK TAHU TEMPE KOTA SEMARANG - Nova Intan Kurniasari; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
This study aims to evaluate the implementation of the Gumregah Tofu and Tempeh Thematic Village Program in Neighborhood Association (RW) 7, Lamper Tengah Village, Semarang City, using William N. Dunn's six policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research method used was qualitative, with data collected through interviews, observation, and documentation with tofu and tempeh entrepreneurs, Semarang City Regional Development Planning Agency (Bappeda) officials and the village administration, and the local community. The results indicate that the thematic village program is conceptually relevant to the characteristics and potential of the region, but its implementation has not yet had a significant impact on increasing the capacity and economic independence of entrepreneurs and the wider community. Overall, the Gumregah Lamper Tengah Thematic Village Program has not been optimal in promoting local-based economic empowerment due to weak sustainability, mentoring, and active community involvement in all program stages.